A Review on the Morphology, Nutritional Value, Traditional Uses, Phytochemistry, and Biological Activities of Pycnarrhena cauliflora and Its Synonyms - Muhammad Farhan Syakir Nor Azman; Nur Amira Zahidah Zainurin; Adiez Sapura Azmi; Monica Suleiman; Ng, Shean Yeaw; Fatimah Salim (Akademi Sains Malaysia, 2022)
The leaves of Pycnarrhena cauliflora, locally known as ‘pokok Ajinomoto’, are consumed as flavour enhancers by East Malaysian communities. The plant also plays a significant role in traditional medicine especially to treat snake bites, eye irritation, headache, and seizures. An extensive literature search on the species revealed that besides taxonomic description as well as toxicity against HeLa human cervical and breast cancer cell lines, there is no report on the plant chemistry. The species has nevertheless been classified as the synonym of several other species which are Antitaxis cauliflora Miers., Pycnarrhena longifolia, (Decne. ex Miq.), Antitaxis longifolius (Decne. ex Miq.) Mier., and Gabila longifolia (Decne. ex Miq, B). Among these synonyms, the plant is closely related to the species P. longifolia. Thus, a complete review of P. cauliflora and its synonyms is important to revise and evaluate its potential for further studies and commercialisation. The information on the species was collected from scientific journals, books, and reports searched through available databases such as Google Scholar, PubMed, Directory of Open Access Journals, Science Direct, Bioline International and Reaxys. This review provides an insight on the morphology, nutritional value, traditional uses, phytochemistry, and biological activities of P. cauliflora and its synonyms published between 1981 to 2021 in scientific journals, books, and reports.